Prediction of gas holdup in partially aerated bubble columns using an EE-LES coupled model. (18th May 2020) - Zhu, S.J.; Ooi, A.; Manasseh, R.; Skvortsov, A.
Highlights: The one-equation SGS model gave better predictions than the Smagorinsky model. Different interfacial force closures were investigated and compared. The EE-LES model can accurately predict the global gas holdup to a very high value. The global gas holdup increases linearly with the superficial gas velocity. A multivariate regression model was proposed to predict the global gas holdup. Abstract: Transient gas-liquid flow dynamics in partially aerated square cross-sectioned bubble columns were studied using an Eulerian–Eulerian based large eddy simulation approach. The numerical model was validated with the interfacial closures evaluated for drag, lift and virtual mass forces. The simulation data showed good agreement with both numerical predictions and experimental measurements in the literature. The current model was also shown to be able to predict the global gas holdup in the bubble column up to a very high value. Further simulations were performed to study the influences of initial liquid phase height to width ratio and inlet area to column cross-sectional area ratio on the global gas holdup in the bubble column. The numerical results indicated that the global gas holdup increases linearly with the superficial gas velocity. Thus, an empirical multivariate regression model was proposed to predict the global gas holdup with an adjusted R-square value of 0.99.